Grading method of heavy oil hydrotreating catalyst
By controlling the number of layers and pore structure of the metal sheet crystals of the catalyst active phase in the grading of heavy oil hydrotreatment catalysts, the problem of poor catalyst activity stability in the prior art is solved, and efficient sulfur and nitrogen removal and aromatic retention are achieved. , extends the service life of the catalyst.
Patent Information
- Application Number
- CN202310957325.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-01
AI Technical Summary
The existing catalyst grading system is difficult to remove impurities such as sulfur and nitrogen at the same time during heavy oil hydrotreatment and maintain the high activity stability of the catalyst, resulting in a shortening of the catalyst service life and an increase in the cost of hydrotreatment.
Using a grading method for heavy oil hydrotreating catalysts, the hydrogenation pretreatment agent, the hydrogenation transition agent and the hydrofining agent are successively filled in the reactor from top to bottom to ensure that the catalyst active metal content gradually increases and controls the The number of layers and pore structures of the active phase metal sheet crystals to achieve effective sulfur, nitrogen removal and aromatic retention.
The demetalization, desulfurization and nitrogen removal activities and stability of the catalyst are improved, and the aromatic content changes are small, the aromatic retention rate is high, and the service life of the catalyst is extended, reducing the operating cost of the hydrogenation device.
Smart Images

Figure BDA0004370326640000201 
Figure BDA0004370326640000211 
Figure BDA0004370326640000212
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst grading method, in particular to a heavy oil hydroprocessing catalyst grading method. Background Art
[0002] Heavy oils such as residual oil, catalytic cracking oil slurry and coking gas oil have high contents of polycyclic aromatic hydrocarbons and colloids, and can be used as high-quality raw materials for the production of high-end carbon materials, with broad market prospects. However, they contain a large amount of heteroatom compounds such as sulfur and nitrogen. The content of these impurities must be reduced to a certain range before high-end carbon materials with qualified physical and chemical indicators can be processed. At present, the main research hotspots are hydroprocessing, which uses selective desulfurization catalysts to remove sulfur and nitrogen from the raw materials while retaining as many aromatics as possible, and then converting them into high-quality carbon materials during the carbonization process. However, there are few reports on extending the operating time of heavy oil hydroprocessing units and improving the service life of catalysts. In the process of hydroprocessing of heavy oil, the stability of the system itself is crucial, and the instability of the heavy oil system hinders the improvement of the conversion rate during the hydrogenation process. The increase in the mass fraction of colloids and aromatic components is conducive to the improvement of the stability of heavy oil colloids. If the reaction occurs, the colloid, heavy aromatics and other macromolecules decompose too quickly, or the products of the initial decomposition do not diffuse away from the catalyst surface in time, it will lead to excessive conversion of heavy oil macromolecules, rapid decrease in aromatic content, instantaneous deterioration of heavy oil colloid stability, and large amounts of heavy components concentrated on the catalyst, resulting in rapid coking and deactivation, poor catalyst activity stability, reduced service life, shortened catalyst operation cycle, and increased hydroprocessing costs. The existing catalyst grading system is difficult to meet the requirements of heavy oil such as residual oil, catalytic cracking slurry and coker wax oil for hydrogenation removal of sulfur, nitrogen and other impurities while maintaining high catalyst activity and stability.
[0003] Chinese patent CN103013567B discloses a method for producing needle coke raw materials from catalytic cracking oil slurry, wherein a protection zone and a hydrogenation reaction zone are set, wherein the protection zone is filled with an adsorbent that can adsorb catalytic cracking catalyst powder, and the hydrogenation reaction zone is filled with a hydrogenation protective agent, a hydrogenation demetallization agent, and a hydrogenation desulfurization agent in sequence according to the flow direction of the reactant stream. In the hydrogenation catalyst grading of the patent, due to the large number of metal platelets of the hydrodesulfurization agent at the rear end and the high intrinsic activity of hydrogenation, it is easy to cause a violent reaction, a rapid catalyst deactivation, and a shortened catalyst life cycle.
[0004] Chinese patent CN 114984970 A discloses a grading method and application of a desolidified catalytic oil slurry hydrodesulfurization catalyst. The grading method comprises: when the sulfur content of the desolidified catalytic oil slurry is ≥0.8% and the content of three-ring and four-ring aromatic hydrocarbons is ≥55%, the reactor is sequentially loaded with a selective dearomatization catalyst, a direct desulfurization catalyst and a hydrodesulfurization catalyst from top to bottom; when the sulfur content of the desolidified catalytic oil slurry is 0.35-0.8% and the content of three-ring and four-ring aromatic hydrocarbons is 40-55%, the reactor is sequentially loaded with a direct desulfurization catalyst and a hydrodesulfurization catalyst from top to bottom. The grading method described in the invention achieves efficient desulfurization while retaining as many three-ring and four-ring aromatic hydrocarbons in the desolidified catalytic oil slurry as possible. The selective dearomatization catalyst used in the patent's hydrogenation catalyst grading method has too small pores. After shallow polycyclic aromatic hydrocarbon saturation and ring opening, the active pores are quickly blocked, which seriously affects the metal activity in the pores. The catalyst is prone to excessive initial coking and rapid deactivation, which in turn affects the operating cycle of the hydrogenation unit.
[0005] Chinese patent CN 111073689 A discloses a heavy oil hydroprocessing method, including the following contents: heavy oil feedstock enters a hydrogenation reactor, contacts a hydrogenation catalyst bed layer for hydrogenation reaction, and the reaction product flows out of the reactor; wherein the hydrogenation catalyst bed layer is graded and loaded with at least two levels of sulfurized hydrogenation catalyst along the logistics direction, and each level of sulfurized hydrogenation catalyst has an average length of metal active phase crystals increasing step by step, an average number of crystals decreasing step by step, an active component content increasing step by step, and a few pore diameter decreasing step by step along the logistics direction. The method of the present invention adopts a specific catalyst grading to effectively utilize the catalyst active center, improve the coupling reaction performance of the active center structure and the reactant molecular structure, and greatly improve the stability of the hydrogenation reaction of the entire system, such as demetallization, desulfurization, denitrogenation, etc. The patented hydrogenation catalyst grading method will result in the catalyst having a large number of front-end lamellae layers, high intrinsic hydrogenation activity, and simultaneous deep hydrogenation desulfurization and dearomatization of heavy oil, which will cause the instantaneous stability of the hydrogenated heavy oil to deteriorate, the catalyst to coke quickly, and the operating cycle of the hydrogenation unit to be shortened. In addition, the aromatic content in the hydrogenated product cannot be guaranteed. In addition, the catalyst in this technology uses an average number of lamellae layers within a certain range, which cannot ensure that each lamellae layer of the catalyst is within this range, and includes lamellae layers that are too large or too small, which can easily cause problems such as severe carbon deposition and rapid deactivation of the catalyst.
[0006] Chinese patent CN 111196934 B discloses a grading method for heavy oil hydroprocessing catalysts, wherein the reactor is sequentially loaded with hydrodemetallization catalyst, hydrodesulfurization catalyst and hydrodenitrogenation catalyst from top to bottom, and the raw material flow is from top to bottom, and is maintained along the flow direction, the catalyst activity gradually increases, the pore size gradually decreases, the particle size gradually decreases, and the porosity gradually decreases; the hydrodemetallization catalyst, the hydrodesulfurization catalyst and the hydrodenitrogenation catalyst are independently composed of one or more catalysts, and the active metal MoS2 in the hydrodemetallization catalyst, the hydrodesulfurization catalyst and the hydrodenitrogenation catalyst after sulfidation is highly dispersed, and the MoS2 in the hydrodemetallization catalyst after sulfidation is mainly dispersed in single layer and double layer, and the MoS2 in the hydrodesulfurization catalyst after sulfidation is mainly dispersed in double layer. The catalyst grading combination obtained by this method has high demetallization, carbon residue removal, desulfurization, denitrification activity and stability, and long service life. The patented hydrogenation catalyst grading method performs simultaneous deep hydrogenation desulfurization and dearomatization of heavy oil, but cannot perform selective desulfurization. The aromatic content in the hydrogenation product is greatly reduced, and it cannot be directly used as a raw material for producing carbon materials.
[0007] Chinese patent CN 105623717 A discloses a hydrogenation catalyst grading method, which comprises: sequentially loading a hydrogenation protection catalyst, a hydrodemetallization catalyst, a hydrodesulfurization catalyst, a hydrodenitrogenation catalyst and / or a hydrodecarbonation catalyst along the direction of logistics, wherein each of the hydrodemetallization catalyst, the hydrodesulfurization catalyst, the hydrodenitrogenation catalyst and the hydrodecarbonation catalyst contains at least part of a bimodal pore catalyst; and along the direction of logistics, in each of the bimodal pore catalysts, the most probable pore diameters of the small pore peak and the large pore peak are gradually reduced, the proportion of the pore volume of the small pore peak in the total pore volume is gradually increased, and the proportion of the pore volume of the large pore peak in the total pore volume is gradually reduced. The present invention also discloses a method for heavy oil hydrotreating using the above-mentioned hydrogenation catalyst grading method. The method disclosed in the present invention can improve the impurity removal rate and extend the operating cycle of the heavy oil hydrogenation unit. The patented hydrogenation catalyst grading method, the catalyst pore structure and the number of layers of active phase crystals enable simultaneous deep hydrogenation desulfurization and dearomatization of heavy oil, but cannot selectively desulfurize, and the effects of desulfurization and removal of residual carbon and nitrogen are also average. The aromatic content in the hydrogenation product is greatly reduced, and it cannot be directly used as a raw material for the production of carbon materials. Summary of the invention
[0008] The object of the present invention is to provide a grading method for heavy oil hydroprocessing catalysts, which effectively exerts the effects of various catalysts, protects the stability of the heavy oil system during the hydroprocessing process to a large extent, improves the demetallization, desulfurization and denitrogenation activity and stability of the catalyst, and ensures that the aromatics content changes little, the aromatics retention rate is high, and the catalyst has a long service life.
[0009] To achieve the above object, the present invention provides a grading method for a heavy oil hydroprocessing catalyst, the method comprising: loading a hydrogenation pretreatment agent, a hydrogenation transition agent, and a hydrogenation finishing agent in a reactor from top to bottom, and keeping the catalyst active metal content gradually increasing along the direction of the raw material flow from top to bottom;
[0010] The number of layers of the active phase metal lamellae of the hydrogenation pretreatment agent after sulfurization is all within the range of 1.0 to 2.0 layers, and the pore volume of the catalyst pores with a diameter of 120nm to 320nm accounts for 10% to 25% of the total pore volume. If the proportion of the pore volume with a diameter of 120nm to 320nm to the total pore volume is too low, it will affect the diffusion of macromolecules, and if the proportion of the pore volume with a diameter of 120nm to 320nm to the total pore volume is too high, it will affect the effective reaction activity specific surface area; the number of layers of the active phase metal lamellae of the hydrogenation pretreatment agent after sulfurization is all within the range of 1.0 to 2.0 layers. If the number of layers of the active phase metal lamellae after sulfurization is higher than 2.0 layers, it is easy to have high initial reaction activity, the stability of heavy oil colloid becomes worse instantly, and a large amount of heavy components are concentrated and precipitated on the catalyst, resulting in rapid coking and deactivation, and poor catalyst activity stability.
[0011] The number of layers of the active phase metal lamellae of the hydrogenation transition agent after sulfurization is all within the range of 3.0 to 4.5 layers, and the pore volume of the catalyst pores with a diameter of 6nm to 15nm accounts for 40% to 65% of the total pore volume. If the proportion of the pore volume with a diameter of 6nm to 15nm to the total pore volume is too low, the effective active reaction space will be affected, and if the proportion of the pore volume with a diameter of 6nm to 15nm to the total pore volume is too high, excessive reaction of intermediate products will occur, coking will increase, and the aromatic content will decrease; the number of layers of the active phase metal lamellae of the hydrogenation transition agent after sulfurization is all within the range of 3.0 to 4.5 layers, if the number of lamellae is less than 3.0 layers, the desulfurization activity will decrease, and if the number of lamellae is more than 4.5 layers, aromatics will be oversaturated and the aromatic content will decrease.
[0012] The number of layers of active phase metal lamellae in the hydrogenated refined agent after sulfurization is all within the range of 1.0 to 2.0 layers, and the pore volume of catalyst pores with a diameter of 6nm to 13nm accounts for 40% to 60% of the total pore volume. If the proportion of pore volume with a diameter of 6nm to 13nm in the total pore volume is too low, the reaction space of sulfur-containing and nitrogen-containing molecules is affected, and the desulfurization and denitrification activities are reduced. If the proportion of pore volume with a diameter of 6nm to 13nm in the total pore volume is too high, the problem of deep removal of aromatics and a significant decrease in content occurs; the number of layers of active phase metal lamellae in the hydrogenated refined agent after sulfurization is all within the range of 1.0 to 2.0 layers. If the number of lamellae is higher than 2.0 layers, the disadvantage of increased coke generation due to condensation of aromatics occurs.
[0013] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein, in the grading method, by weight percentage, the hydrogenation pretreatment agent accounts for 10% to 30%, the hydrogenation transition agent accounts for 20% to 45%, and the hydrogenation finishing agent accounts for 40% to 70%.
[0014] In the grading method of the heavy oil hydroprocessing catalyst of the present invention, the sulfurization process of the hydrogenation pretreatment agent, the hydrogenation transition agent and the hydrogenation finishing agent is not particularly limited, and they can be independently selected from dry sulfurization or wet sulfurization.
[0015] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein the sulfiding agent in the sulfiding process of the hydrogenation pretreatment agent, the hydrogenation transition agent and the hydrogenation finishing agent is independently selected from at least one of H2S, mercaptans, disulfides, polysulfides and thiophenecarboxylic acid compounds; preferably, further independently selected from at least one of H2S, carbon disulfide, dimethyl sulfide and dimethyl disulfide.
[0016] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein, preferably, the hydrogenation pretreatment agent uses an inorganic oxide as a carrier, uses a VIB group metal and / or a VIII group metal as an active component, and based on the weight of the catalyst, the active metal is calculated as oxide, the VIB group metal is 3wt% to 26wt%, preferably 4.0wt% to 8.0wt%, and the VIII group metal is 0.5wt% to 8wt%, preferably 0.8wt% to 2.2wt%.
[0017] In the grading method of the heavy oil hydroprocessing catalyst of the present invention, the hydroprocessing pretreatment agent preferably also includes an auxiliary agent, and the auxiliary agent is selected from at least one of P, Si, F, and B.
[0018] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein, preferably, the hydrogenation transition agent uses an inorganic oxide as a carrier, uses a VIB group metal and / or a VIII group metal as an active component, and based on the weight of the catalyst, the active metal is calculated as oxide, the VIB group metal is 3wt% to 26wt%, preferably 9.0wt% to 15.0wt%, and the VIII group metal is 0.5wt% to 8wt%, preferably 2.3wt% to 4.5wt%.
[0019] In the grading method of the heavy oil hydroprocessing catalyst of the present invention, the hydrogenation transition agent preferably also includes an auxiliary agent, and the auxiliary agent is selected from at least one of P, Si, F, and B.
[0020] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein, preferably, the hydroprocessing refining agent uses an inorganic oxide as a carrier, uses a VIB group metal and / or a VIII group metal as an active component, and based on the weight of the catalyst, the active metal is calculated as oxide, the VIB group metal is 3wt% to 26wt%, preferably 16.0wt% to 22.0wt%, and the VIII group metal is 0.5wt% to 8wt%, preferably 3.0wt% to 6.0wt%.
[0021] In the grading method of the heavy oil hydroprocessing catalyst of the present invention, the hydrofining agent preferably also includes an auxiliary agent, and the auxiliary agent is selected from at least one of P, Si, F, and B.
[0022] In the grading method of the heavy oil hydroprocessing catalyst of the present invention, it is preferred that the inorganic oxide is selected from at least one of aluminum oxide and silicon oxide, the VIB Group metal is selected from at least one of W and Mo, and the VIII Group metal is selected from at least one of Co and Ni.
[0023] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein the conditions of the heavy oil hydroprocessing are preferably: hydrogen pressure 3.0MPa-18.0MPa, temperature 280℃-420℃, liquid hourly volume space velocity 0.15h -1 ~3.5h -1 , hydrogen to oil volume ratio is 300~2000.
[0024] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein the conditions of the heavy oil hydroprocessing are further preferably: hydrogen pressure 5.0MPa-16.0MPa, temperature 300℃-390℃, liquid hourly volume space velocity 0.2h -1 ~2.5h -1 , hydrogen to oil volume ratio 400~1800.
[0025] The grading method of the heavy oil hydroprocessing catalyst of the present invention, wherein the sources of the hydroprocessing pretreatment agent, the hydroprocessing transition agent and the hydroprocessing finishing agent are not particularly limited, and they can be selected from conventional commercial catalysts in the art or prepared by conventional methods of the prior art, for example, the following catalyst preparation method is adopted: the alumina carrier is saturated with a solution containing active metal components to obtain a catalyst precursor, and the desired oxidation state hydrogenation catalyst is obtained after drying and calcining. Wherein, the drying temperature is 90°C to 260°C, preferably 100°C to 200°C, the drying time is 1h to 7h, preferably 3h to 5h; the calcination temperature is 400°C to 600°C, preferably 450°C to 560°C, and the calcination time is 1h to 7h, preferably 3h to 5h.
[0026] The grading method of the present invention can be used in a conventional fixed-bed hydrogenation device. During the actual use of the grading method of the present invention, the heavy oil feedstock and hydrogen are mixed and then enter the hydrogenation device and sequentially pass through a supporting protective agent, a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation refining agent. The oil and gas after the reaction enter a subsequent separation device for separation.
[0027] The present invention has discovered a heavy oil hydrogenation catalyst grading method that can effectively selectively desulfurize and delay coking. The catalyst grading combination of the present invention gives full play to the physical and chemical characteristics of several catalysts, has good activity and stability in removing impurities such as sulfur and nitrogen, has a high aromatics retention rate, slows down the deactivation rate of the catalyst, and prolongs the operation cycle of the catalyst, which shows some beneficial use effects that existing catalyst gradings cannot have. The hydrogenation pretreatment agent has low intrinsic activity, contains a small amount of large pores, and has a small number of metal active sites. It has the function of improving the stability of heavy oil and shallow conversion, and prevents rapid coking and deactivation. The hydrogenation transition agent has a large number of active metal lamellae, high intrinsic hydrogenation desulfurization activity, and a suitable pore distribution, which reduces the steric hindrance effect, so that sulfur-containing macromolecules with large steric hindrance open the ring or break the chain, and there are few active sites acting on aromatics hydrogenation saturation, and the reaction products diffuse away from the catalyst surface in time to avoid deep reaction. The hydrogenation refining agent has a small number of active metal lamellae, a large number of metal active sites, and a suitable pore size distribution. It is mainly based on direct hydrogenation desulfurization to achieve a selective deep desulfurization effect.
[0028] The catalysts in the prior art use an average number of lamellae within a certain range, but some of them contain too large or too small lamellae, which can easily cause serious carbon deposition and rapid deactivation of the catalyst. After discovering this problem during the research process, the inventors innovatively adopted the range of 1.0 to 2.0 layers of active phase metal lamellae after sulfurization of the hydrogenation pretreatment agent, the range of 3.0 to 4.5 layers of active phase metal lamellae after sulfurization of the hydrogenation transition agent, and the range of 1.0 to 2.0 layers of active phase metal lamellae after sulfurization of the hydrogenation refining agent, thereby solving the technical problems of serious carbon deposition and rapid deactivation of the catalysts in the prior art.
[0029] The macromolecules such as colloid and heavy aromatics in the heavy oil are slowly decomposed by the pretreatment agent containing large unobstructed pores and low intrinsic activity. The initial decomposition products quickly leave the catalyst surface and then pass through the transition agent with relatively more active metal platelets, higher intrinsic hydrodesulfurization activity, suitable pore distribution, and moderate number of active sites. By reducing the steric hindrance effect, the ring opening or chain breaking of sulfur-containing macromolecules is promoted to form a moderate reaction, and finally enter the refining agent treatment area with a large number of metal active sites, suitable pore distribution, and direct hydrogenation desulfurization as the main method. While greatly reducing the content of impurities such as sulfur and nitrogen, it effectively slows down the condensation of polycyclic aromatic hydrocarbons to form coke, achieves selective deep desulfurization, ensures that the aromatic content changes little, and the heavy oil system always maintains a high stability, thereby extending the service life of the catalyst and reducing the operating cost of the hydrogenation unit. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a transmission electron microscope image of the hydrogenation pretreatment agent of Example 1 of the present invention.
[0031] Figure 2 This is a transmission electron microscope image of the hydrogenation transition agent of Example 1 of the present invention.
[0032] Figure 3 This is a transmission electron microscope image of the hydrogenation refining agent of Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The method of the present invention is described in detail below in conjunction with specific examples, but the scope of protection of the present invention is not limited thereto. wt% is mass fraction.
[0034] Analytical methods:
[0035] The number of lamellae of the sulfided catalyst was statistically analyzed by transmission electron microscopy (TEM) (the average value was obtained by manual statistics of 30 TEM images); JEOL 2100PLus high-resolution transmission electron microscope, magnification 250K, acceleration voltage 200kV, LaB filament, line resolution 0.14nm, point resolution 0.23nm.
[0036] The pore volume and pore size distribution of the catalyst were measured by low temperature liquid nitrogen adsorption method, and the instrument used was American Micrometeritics ASAP 2010 automatic adsorption instrument. The pore size distribution of the catalyst was measured by BJH method.
[0037] Example 1
[0038] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing active components of MoO3 and NiO to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 4.1wt% MoO3 and 3.1wt% NiO, and the pore volume with a diameter of 120nm to 320nm accounts for 15% of the total pore volume.
[0039] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 110°C for 6 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 13.1wt%, a NiO content of 1.2wt%, a P2O5 content of 4.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 50% of the total pore volume.
[0040] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 550°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 20.5wt%, a CoO content of 5wt%, a P2O5 content of 0.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 42% of the total pore volume.
[0041] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0042] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0043] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 15%, 20% and 65% respectively.
[0044] Example 2
[0045] Preparation of hydrogenation pretreatment agent: same as in Example 1.
[0046] Preparation of hydrogenation transition agent: same as in Example 1.
[0047] Preparation of hydrogenation refined agent: same as Example 1.
[0048] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0049] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0050] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 25%, 30% and 45% respectively.
[0051] Example 3
[0052] Preparation of hydrogenation pretreatment agent: The silicon-containing carrier is saturated with a solution containing MoO3 and NiO active components to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 7.5wt% MoO3, 2.0wt% NiO, 0.5wt% SiO2, and the pore volume with a diameter of 120nm to 320nm accounts for 11% of the total pore volume.
[0053] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 10.0wt%, a NiO content of 2.5wt%, a P2O5 content of 3.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 58% of the total pore volume.
[0054] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3 and CoO active components to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 17.0wt%, a CoO content of 4.1wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 52% of the total pore volume.
[0055] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0056] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0057] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 10%, 35% and 55% respectively.
[0058] Example 4
[0059] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing MoO3, NiO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 3.7wt% MoO3, 0.8wt% NiO, 0.3wt% P2O5, and the pore volume with a diameter of 120nm to 320nm accounts for 23% of the total pore volume.
[0060] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 110°C for 6 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 9.7wt%, a NiO content of 2.1wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 62% of the total pore volume.
[0061] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 550°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 12.6wt%, a CoO content of 3.1wt%, a P2O5 content of 3.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 60% of the total pore volume.
[0062] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0063] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0064] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 25%, 30% and 45% respectively.
[0065] Example 5
[0066] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing active components of MoO3 and NiO to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 8.0wt% MoO3 and 2.0wt% NiO, and the pore volume with a diameter of 120nm to 320nm accounts for 18% of the total pore volume.
[0067] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 110°C for 6 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 13.6wt%, a NiO content of 4.5wt%, a P2O5 content of 3.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 42% of the total pore volume.
[0068] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 550°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 21.2wt%, a CoO content of 3.5wt%, a P2O5 content of 5.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 55% of the total pore volume.
[0069] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0070] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0071] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 15%, 20% and 65% respectively.
[0072] Example 6
[0073] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing active components of MoO3 and NiO to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 12.0wt% MoO3 and 2.1wt% NiO, and the pore volume with a diameter of 120nm to 320nm accounts for 20% of the total pore volume.
[0074] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 110°C for 6 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 18.0wt%, a NiO content of 3.3wt%, a P2O5 content of 5.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 47% of the total pore volume.
[0075] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 550°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 21.0wt%, a CoO content of 5.7wt%, a P2O5 content of 3.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 52% of the total pore volume.
[0076] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0077] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0078] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 15%, 20% and 65% respectively.
[0079] Example 7
[0080] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing WO3 and CoO active components to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 12.0wt% WO3 and 2.1wt% CoO, and the pore volume with a diameter of 120nm to 320nm accounts for 20% of the total pore volume.
[0081] Preparation of hydrogenation transition agent: The carrier containing B is saturated with a solution containing WO3 and CoO active components to obtain a catalyst precursor, which is dried at 110°C for 6 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a WO3 content of 18.0wt%, a CoO content of 3.3wt%, a B2O3 content of 1.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 52% of the total pore volume.
[0082] Preparation of hydrogenation refining agent: The carrier containing Si is saturated with a solution containing WO3, NiO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 550°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a WO3 content of 21.0wt%, a NiO content of 5.7wt%, a SiO2 content of 0.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 58% of the total pore volume.
[0083] Then, dry vulcanization was adopted, DMDS was used as the vulcanizing agent, the pressure of the vulcanization process was 16MPa, the circulating hydrogen volume was 300L / h, the vulcanization conditions were constant temperature at 230°C for 10h, constant temperature at 280°C for 4h, constant temperature at 320°C for 6h, and the heating rate was 10°C / h.
[0084] The active metal platelets of the hydrogenation pretreatment agent after sulfidation are all 1.0 to 2.0 layers; the active metal platelets of the hydrogenation transition agent after sulfidation are all 3.0 to 4.5 layers; and the active metal platelets of the hydrogenation finishing agent after sulfidation are all 1.0 to 2.0 layers.
[0085] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 15%, 20% and 65% respectively.
[0086] Comparative Example 1
[0087] Referring to Example 1 of CN 111073689 A, the following catalyst grading method was adopted.
[0088] Hydrogenation catalyst I: MoO3 content is 12.0wt%, NiO content is 2.1wt%, and the pore volume with a diameter of 120nm to 320nm accounts for 5% of the total pore volume.
[0089] Hydrogenation catalyst II: MoO3 content is 18.0wt%, NiO content is 3.3wt%, and the pore volume with a diameter of 6nm to 15nm accounts for 75% of the total pore volume.
[0090] Hydrogenation catalyst III: MoO3 content is 21.0wt%, NiO content is 5.7wt%, and the pore volume with a diameter of 6nm to 13nm accounts for 85% of the total pore volume.
[0091] The vulcanization conditions are the same as those in Example 1 of CN 111073689 A.
[0092] The average number of active phase metal lamellae of the sulfurized hydrogenation catalyst I is 8.7, of which lamellae 8.0 accounts for 60% of all lamellae, lamellae 9.0 accounts for 20%, lamellae 10.0 accounts for 10%, and lamellae 11.0 accounts for 10% of all lamellae; the average number of active phase metal lamellae of the sulfurized hydrogenation catalyst II is 5.7, of which lamellae 4.0 accounts for 20% of all lamellae, lamellae 5.0 accounts for 50% of all lamellae, and lamellae 8.0 accounts for 30% of all lamellae; the average number of active phase metal lamellae of the sulfurized hydrogenation catalyst III is 2.4, of which lamellae 1.0 accounts for 20% of all lamellae, lamellae 2.0 accounts for 50% of all lamellae, and lamellae 4 accounts for 30% of all lamellae.
[0093] The bed layer in the reactor is filled with hydrogenation catalyst I, hydrogenation catalyst II and hydrogenation catalyst III in order from top to bottom, and the added mass proportions are 20%, 30% and 50% respectively.
[0094] Comparative Example 2
[0095] Referring to Comparative Example 1 of CN 111073689 A, the following catalyst grading method was adopted.
[0096] Hydrogenation catalyst I: MoO3 content is 12.0wt%, NiO content is 2.7wt%, and the pore volume with a diameter of 120nm to 320nm accounts for 5% of the total pore volume.
[0097] Hydrogenation catalyst II: MoO3 content is 18.7wt%, NiO content is 4.6wt%, and the pore volume with a diameter of 6nm to 15nm accounts for 75% of the total pore volume.
[0098] Hydrogenation catalyst III: MoO3 content is 24.5wt%, NiO content is 6.7wt%, and the pore volume with a diameter of 6nm to 13nm accounts for 72% of the total pore volume.
[0099] The vulcanization conditions were the same as those of Comparative Example 1 of CN 111073689 A.
[0100] The average number of active metal lamellae of the sulfurized hydrogenation catalyst I is 7.9, of which lamellae 7.0 accounts for 40% of all lamellae, lamellae 8.0 accounts for 40% of all lamellae, lamellae 9.0 accounts for 10% of all lamellae, and lamellae 10.0 accounts for 10% of all lamellae. The average number of active metal lamellae of the sulfurized hydrogenation catalyst II is 8.8, of which lamellae 7.0 accounts for 20% of all lamellae, lamellae 8.0 accounts for 40% of all lamellae, lamellae 10.0 accounts for 20% of all lamellae, and lamellae 11.0 accounts for 20% of all lamellae; the average number of active metal lamellae of the sulfurized hydrogenation catalyst III is 8.2, of which lamellae 7.0 accounts for 20% of all lamellae, lamellae 8.0 accounts for 40% of all lamellae, and lamellae 9.0 accounts for 40% of all lamellae.
[0101] The bed layer in the reactor is filled with hydrogenation catalyst I, hydrogenation catalyst II and hydrogenation catalyst III in order from top to bottom, and the added mass proportions are 20%, 30% and 50% respectively.
[0102] Comparative Example 3
[0103] Referring to Comparative Example 2 of CN 111073689 A, the following catalyst grading method was adopted.
[0104] Hydrogenation catalyst I: MoO3 content is 11.2wt%, NiO content is 2.9wt%, and the pore volume with a diameter of 120nm to 320nm accounts for 6% of the total pore volume.
[0105] Hydrogenation catalyst II: MoO3 content is 20.0wt%, NiO content is 3.7wt%, and the pore volume with a diameter of 6nm to 15nm accounts for 88% of the total pore volume.
[0106] Hydrogenation catalyst III: MoO3 content is 24.8wt%, NiO content is 5.7wt%, and the pore volume with a diameter of 6nm to 13nm accounts for 80% of the total pore volume.
[0107] The vulcanization conditions were the same as those in Comparative Example 2 of CN 111073689 A.
[0108] The average number of active metal lamellae of the sulfurized hydrogenation catalyst I is 4.0, of which lamellae 1.0 accounts for 10% of all lamellae, lamellae 2.0 accounts for 10% of all lamellae, lamellae 3.0 accounts for 10% of all lamellae, lamellae 4.0 accounts for 50% of all lamellae, lamellae 5.0 accounts for 10% of all lamellae, and lamellae 9.0 accounts for 10% of all lamellae. The average number of active metal lamellae of the sulfurized hydrogenation catalyst II is 4.5, of which lamellae 2.0 accounts for 10% of all lamellae, lamellae 3.0 accounts for 10% of all lamellae, lamellae 4.0 accounts for 40% of all lamellae, and lamellae 6.0 accounts for 40% of all lamellae. The average number of active phase metal lamellae of the sulfurized hydrogenation catalyst III is 5.2, of which lamellae 3.0 account for 20% of all lamellae, lamellae 5.0 account for 40% of all lamellae, lamellae 6.0 account for 20% of all lamellae, and lamellae 7.0 account for 20% of all lamellae.
[0109] The bed layer in the reactor is filled with hydrogenation catalyst I, hydrogenation catalyst II and hydrogenation catalyst III in order from top to bottom, and the added mass proportions are 20%, 30% and 50% respectively.
[0110] Comparative Example 4
[0111] Referring to Comparative Example 3 of CN 111073689 A, the following catalyst grading method was adopted.
[0112] Hydrogenation catalyst I: MoO3 content is 11.5wt%, NiO content is 2.8wt%, and the pore volume with a diameter of 120nm to 320nm accounts for 9% of the total pore volume.
[0113] Hydrogenation catalyst II: MoO3 content is 20.5wt%, NiO content is 3.8wt%, and the pore volume with a diameter of 6nm to 15nm accounts for 80% of the total pore volume.
[0114] Hydrogenation catalyst III: MoO3 content is 25.8wt%, NiO content is 5.5wt%, and the pore volume with a diameter of 10nm to 15nm accounts for 92% of the total pore volume.
[0115] The vulcanization conditions were the same as those in Comparative Example 3 of CN 111073689 A.
[0116] The average number of active phase metal lamellae of the sulfurized hydrogenation catalyst I is 2.5, of which lamellae 1.0 accounts for 20% of all lamellae, lamellae 2.0 accounts for 40% of all lamellae, lamellae 3.0 accounts for 10% of all lamellae, and lamellae 4.0 accounts for 30% of all lamellae. The average number of active phase metal lamellae of the sulfurized hydrogenation catalyst II is 2.8, of which lamellae 2.0 accounts for 50% of all lamellae, lamellae 3.0 accounts for 20% of all lamellae, and lamellae 4.0 accounts for 30% of all lamellae; the average number of active phase metal lamellae of the sulfurized hydrogenation catalyst III is 3.0, of which lamellae 1.0 accounts for 20% of all lamellae, lamellae 2.0 accounts for 20% of all lamellae, lamellae 3.0 accounts for 20% of all lamellae, lamellae 4.0 accounts for 30% of all lamellae, and lamellae 6.0 accounts for 10% of all lamellae.
[0117] The bed layer in the reactor is filled with hydrogenation catalyst I, hydrogenation catalyst II and hydrogenation catalyst III in order from top to bottom, and the added mass proportions are 20%, 30% and 50% respectively.
[0118] Comparative Example 5
[0119] Referring to Example 2 of CN 105623717 A, the following catalyst grading method was adopted.
[0120] Protective agent: MoO3 content 3.0wt%, NiO content 0.8wt%.
[0121] Demetallizing agent: MoO3 content is 8.4wt%, NiO content is 1.5wt%, and the pore volume with a diameter of 120nm to 320nm accounts for 8% of the total pore volume.
[0122] Desulfurizer: MoO3 content is 16.2wt%, NiO content is 4.5wt%, and the pore volume with a diameter of 6nm to 15nm accounts for 70% of the total pore volume.
[0123] Carbon residue removal agent: MoO3 content is 18.0wt%, NiO content is 5.0wt%, and the pore volume with a diameter of 6nm to 13nm accounts for 65% of the total pore volume.
[0124] The vulcanization conditions are the same as those in Example 1.
[0125] After sulfidation, the proportion of 1.0-2.0 layers of metal lamellae in the active phase of the demetallization agent to all lamellae is 86.5%, and the rest are lamellae with more than 2 layers; the proportion of 1.0-2.0 layers of metal lamellae in the active phase of the desulfurization agent after sulfidation is 20% of all lamellae, the proportion of 3.0-4.5 layers of lamellae is 20%, the proportion of 2.0-3.0 layers of lamellae is 51%, and the rest are lamellae with more than 4.5 layers; the proportion of 1.0-2.0 layers of metal lamellae in the active phase of the decarbonizing agent after sulfidation is 4% of all lamellae, the proportion of 3.0-4.5 layers of lamellae is 60%, and the rest are lamellae with more than 4.5 layers.
[0126] The bed layer in the reactor is filled with a protective agent, a demetallizing agent, a desulfurizing agent and a carbon removal agent in order from top to bottom, and the added mass proportions are 5%, 35%, 30% and 30% respectively.
[0127] Comparative Example 6
[0128] The difference from Example 1 is that the proportion of pore volume of the hydrogenation pretreatment agent with diameter of 120nm to 320nm accounts for 5% of the total pore volume.
[0129] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing active components of MoO3 and NiO to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 4.1wt% MoO3 and 3.1wt% NiO, and the pore volume with a diameter of 120nm to 320nm accounts for 5% of the total pore volume.
[0130] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 110°C for 6 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 13.1wt%, a NiO content of 1.2wt%, a P2O5 content of 4.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 50% of the total pore volume.
[0131] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 550°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 20.5wt%, a CoO content of 5wt%, a P2O5 content of 0.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 42% of the total pore volume.
[0132] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0133] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0134] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 15%, 20% and 65% respectively.
[0135] Comparative Example 7
[0136] The difference from Example 1 is that the pore volume of the hydrogenation transition agent with a diameter of 6 nm to 15 nm accounts for 70% of the total pore volume.
[0137] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing active components of MoO3 and NiO to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 4.1wt% MoO3 and 3.1wt% NiO, and the pore volume with a diameter of 120nm to 320nm accounts for 15% of the total pore volume.
[0138] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 110°C for 6 hours, heated to 450°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 13.1wt%, a NiO content of 1.2wt%, a P2O5 content of 4.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 70% of the total pore volume.
[0139] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 550°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 20.5wt%, a CoO content of 5wt%, a P2O5 content of 0.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 42% of the total pore volume.
[0140] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0141] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0142] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 15%, 20% and 65% respectively.
[0143] Comparative Example 8
[0144] The difference from Example 1 is that the pore volume of the hydrofining agent with a diameter of 6 nm to 13 nm accounts for 72% of the total pore volume.
[0145] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing active components of MoO3 and NiO to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 4.1wt% MoO3 and 3.1wt% NiO, and the pore volume with a diameter of 120nm to 320nm accounts for 15% of the total pore volume.
[0146] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 110°C for 8 hours, heated to 480°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 13.1wt%, a NiO content of 1.2wt%, a P2O5 content of 4.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 50% of the total pore volume.
[0147] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 500°C at 5°C / min, and calcined at a constant temperature for 4 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 20.5wt%, a CoO content of 5wt%, a P2O5 content of 0.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 72% of the total pore volume.
[0148] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0149] After sulfidation, the active metal MoS2 platelets of the hydrogenation pretreatment agent are all 1.0 to 2.0 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation transition agent are all 3.0 to 4.5 layers; after sulfidation, the active metal MoS2 platelets of the hydrogenation finishing agent are all 1.0 to 2.0 layers.
[0150] The bed layer in the reactor is filled with a hydrogenation pretreatment agent, a hydrogenation transition agent and a hydrogenation finishing agent in order from top to bottom, and the added mass proportions are 15%, 20% and 65% respectively.
[0151] Comparative Example 9
[0152] The difference from Example 1 is that the number of active metal MoS2 platelets after sulfurization with the hydrogenated refining agent is only partially within the range of 1.0 to 2.0 layers, the number of active metal MoS2 platelets after sulfurization with the hydrogenated transition agent is only partially within the range of 3.0 to 4.5 layers, and the number of active metal MoS2 platelets after sulfurization with the hydrogenated refining agent is only partially within the range of 1.0 to 2.0 layers.
[0153] Preparation of hydrogenation pretreatment agent: The carrier is saturated with a solution containing active components of MoO3 and NiO to obtain a catalyst precursor, which is dried at 120°C for 5 hours, heated to 520°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation pretreatment agent. The catalyst contains 4.1wt% MoO3 and 3.1wt% NiO, and the pore volume with a diameter of 120nm to 320nm accounts for 15% of the total pore volume.
[0154] Preparation of hydrogenation transition agent: The carrier is saturated with a solution containing MoO3, NiO active components and phosphoric acid to obtain a catalyst precursor, which is dried at 100°C for 5 hours, heated to 490°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation transition agent. The catalyst has a MoO3 content of 13.1wt%, a NiO content of 1.2wt%, a P2O5 content of 4.5wt%, and a pore volume with a diameter of 6nm to 15nm accounting for 50% of the total pore volume.
[0155] Preparation of hydrogenation refining agent: The carrier is saturated with a solution containing MoO3, CoO active components and ammonium phosphate to obtain a catalyst precursor, which is dried at 150°C for 5 hours, heated to 580°C at 5°C / min, and calcined at a constant temperature for 5 hours to obtain a hydrogenation refining agent. The catalyst has a MoO3 content of 20.5wt%, a CoO content of 5wt%, a P2O5 content of 0.8wt%, and a pore volume with a diameter of 6nm to 13nm accounting for 42% of the total pore volume.
[0156] Then, wet vulcanization was adopted, CS2 was used as the vulcanizing agent, the addition amount was 2.0wt%, ordinary four-line diesel was used as the vulcanizing oil, hydrogen was passed once, the vulcanization conditions were constant temperature at 280°C for 20h, constant temperature at 320°C for 8h, and the heating rate was 10°C / h.
[0157] The average number of active metal MoS2 lamellae in the hydrogenation pretreatment agent after sulfurization is 1.0 to 2.0 layers, of which lamellae 1.0 accounts for 50% of all lamellae, lamellae 2.0 accounts for 30% of all lamellae, lamellae 3.0 accounts for 10% of all lamellae, and lamellae 4.0 accounts for 10% of all lamellae. The average number of active metal MoS2 lamellae in the hydrogenation transition agent after sulfurization is 3.0 to 4.5 layers, of which lamellae 1.0 accounts for 10% of all lamellae, lamellae 3.0 accounts for 40% of all lamellae, lamellae 4.0 accounts for 30% of all lamellae, lamellae 5.0 accounts for 10% of all lamellae, and lamellae 5.0 accounts for 10% of all lamellae. The average number of active metal MoS2 lamellae in the hydrogenated refining agent after sulfidation is 1.0 to 2.0 layers, of which lamellae 1.0 accounts for 60% of all lamellae, lamellae 2.0 accounts for 20% of all lamellae, lamellae 3.0 accounts for 10% of all lamellae, and lamellae 4.0 accounts for 10% of all lamellae.
[0158] Example 8
[0159] This example is a comparative test of the activity and stability of the catalyst combination of Examples 1-7 and Comparative Examples 1-9. The evaluation was carried out on a 300 mL small fixed bed hydrogenation device, and the properties of the feedstock oil are shown in Table 1.
[0160] Table 1 Main properties of catalytic cracking slurry
[0161] <![CDATA[Density (20 °C), kg / m 3 > 1100 Sulfur, wt% 1.10 Nitrogen, μg / g 1900 Aromatics, wt% 71.3 Gel, wt% 16.1
[0162] The evaluation conditions are shown in Table 2.
[0163] Table 2 Evaluation process conditions
[0164] Pressure, MPa 8 Hydrogen to oil ratio (volume) 800 Reaction temperature, °C 350 <![CDATA[Liquid hourly space velocity, h -1 > 0.7
[0165] The activity evaluation results of the catalyst combination system after 1000 h of operation are listed in Table 3.
[0166] Table 3 Activity evaluation results of the catalyst combination system after 1000h operation
[0167]
[0168]
[0169] It can be seen from Table 3 that the desulfurization rate and denitrification rate of the catalyst grading combination of the embodiment are higher than those of the catalyst grading combination of the comparative example; the aromatics content of the embodiment is higher than that of the comparative example, which proves that the grading method of the heavy oil hydroprocessing catalyst of the present invention has a better aromatics retention rate.
[0170] The results of the 5000-hour activity stability evaluation are listed in Table 4.
[0171] Table 4 Activity stability evaluation results for 5000 h
[0172]
[0173]
[0174] As can be seen from Table 4, as the operation time increases, the desulfurization rate and denitrification rate of the catalyst graded combination of the embodiment are significantly higher than those of the catalyst combination of the comparative example, and the aromatics content is higher than that of the comparative example, showing excellent decontamination activity stability and aromatics retention rate. This is because the catalyst graded mode of the present invention well realizes the gradient coordination of the number of catalyst active phase crystal layers and the pore structure, achieving the effect of directional and precise reaction of impurities to be removed in the oil slurry.
[0175] Example 9
[0176] This example is a comparative test of the activity and stability of the catalyst combination of Examples 1-7 and Comparative Examples 1-9. The evaluation was carried out on a 300mL small fixed bed hydrogenation device, and the properties of the feedstock oil are shown in Table 5.
[0177] Table 5 Main properties of feedstock oil of a domestic residue oil hydrotreating unit
[0178] <![CDATA[Density (20 °C), kg / m 3 > 959 sulfur,% 1.82 Nitrogen, μg / g 3500 Carbon residue, wt% 8.8 (Ni+V), wt% 30.1
[0179] The evaluation conditions are shown in Table 6.
[0180] Table 6 Evaluation process conditions
[0181] Pressure, MPa 13.0 Hydrogen to oil ratio (volume) 1000 Reaction temperature, °C 375 <![CDATA[Liquid hourly space velocity, h -1 > 0.3
[0182] The activity evaluation results of the catalyst combination system after 1000 hours of operation are listed in Table 7.
[0183] Table 7 Activity evaluation results of the catalyst combination system after 1000h operation
[0184]
[0185]
[0186] It can be seen from Table 7 that the desulfurization rate and denitrification rate of the catalyst grade combination of the embodiment are higher than those of the catalyst grade combination of the comparative example, and the aromatics content is higher than that of the comparative example.
[0187] The results of the 5000-hour activity stability evaluation are listed in Table 8.
[0188] Table 8 Activity stability evaluation results for 5000 h
[0189]
[0190]
[0191] It can be seen from Table 8 that as the operation time increases, the desulfurization rate and denitrification rate of the catalyst grade combination of the embodiment are significantly higher than those of the catalyst combination of the comparative example, and the aromatic content is higher than that of the comparative example, showing excellent activity stability and aromatic retention rate. The catalyst grade combination method of the present invention well realizes the gradient coordination of the number of catalyst active phase crystal layers and the pore structure, achieving the effect of directional and precise reaction of impurities to be removed in heavy oil.
[0192] From the comparison results of Examples 1-7 and Comparative Examples 1-5 in Tables 3, 4, 7 and 8, it can be seen that, compared with the prior art, the grading method of the heavy oil hydroprocessing catalyst of the present invention has higher desulfurization and denitrification activity and stability, better aromatics retention rate, can effectively slow down the deactivation rate of the catalyst, and extend the operation cycle of the catalyst.
[0193] From the comparison results of Example 1 and Comparative Examples 6-8 in Tables 3, 4, 7 and 8, it can be seen that the proportion of pore volumes of each diameter of the hydrogenation pretreatment agent, hydrogenation transition agent and hydrogenation finishing agent all affect the effect of the grading method. If the pore volume proportion is too high or too low, the desulfurization and denitrification activities and stability of the obtained catalyst graded combination are poor, and the aromatics retention rate is low. Within the range of the pore diameter distribution and pore volume proportion of the present invention, the desulfurization and denitrification activities and stability of the obtained catalyst graded combination are higher, the aromatics retention rate is better, the deactivation rate of the catalyst can be effectively slowed down, and the operation cycle of the catalyst can be extended.
[0194] From the comparison results of Example 1 and Comparative Example 9 in Tables 3, 4, 7 and 8, it can be seen that when the average number of active phase metal lamellae after the hydrogenation pretreatment agent, hydrogenation transition agent and hydrogenation refining agent sulfurization is only within the range of 1.0 to 2.0 layers, 3.0 to 4.5 layers and 1.0 to 2.0 layers, respectively, and contains lamellae with other numbers of layers, the resulting catalyst gradation combination is poor. When the number of lamellae of the active phase metal lamellae after the hydrogenation pretreatment agent, hydrogenation transition agent and hydrogenation refining agent sulfurization is all within the range of 1.0 to 2.0 layers, 3.0 to 4.5 layers and 1.0 to 2.0 layers, respectively, the resulting catalyst gradation combination has higher desulfurization and denitrification activity and stability, better aromatics retention rate, can effectively slow down the deactivation rate of the catalyst, and extend the operation cycle of the catalyst.
[0195] In summary, compared with the prior art, the present invention proposes a hydrogenation catalyst graded combination that can effectively exert the effects of various catalysts, and the grading method of the present invention has better effects than the prior art; in the present invention, the pore diameter distribution, pore volume ratio, and number of lamellar layers are all within the selected number of layers, and the obtained catalyst graded combination has higher desulfurization and denitrification activity and stability, better aromatics retention rate, and can effectively slow down the deactivation rate of the catalyst and extend the operating cycle of the catalyst.
[0196] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A grading method for a heavy oil hydroprocessing catalyst, characterized in that: include: The hydrogenation pretreatment agent, hydrogenation transition agent, and hydrogenation finishing agent are sequentially loaded in the reactor from top to bottom, and the raw material flow is from top to bottom, and the active metal content of the catalyst is gradually increased along the flow direction; The hydrogenation pretreatment agent has a number of active phase metal platelets after sulfurization that are all within the range of 1.0 to 2.0 layers, and the pore volume of catalyst pores with a diameter of 120 nm to 320 nm accounts for 10% to 25% of the total pore volume; The hydrogenation transition agent has a number of active phase metal platelets after sulfurization that are all within the range of 3.0 to 4.5 layers, and the pore volume of catalyst pores with a diameter of 6 nm to 15 nm accounts for 40% to 65% of the total pore volume; The hydrogenation refining agent has the number of active phase metal platelets after sulfidation within the range of 1.0 to 2.0 layers, and the pore volume of catalyst pores with a diameter of 6nm to 13nm accounts for 40% to 60% of the total pore volume.
2. The grading method of heavy oil hydroprocessing catalyst according to claim 1, characterized in that: In the grading method, the hydrogenation pretreatment agent accounts for 10% to 30% by weight, the hydrogenation transition agent accounts for 20% to 45% and the hydrogenation finishing agent accounts for 40% to 70%.
3. The grading method of heavy oil hydroprocessing catalyst according to claim 1, characterized in that: The sulfurization processes of the hydrogenation pretreatment agent, the hydrogenation transition agent and the hydrogenation finishing agent are independently selected from dry sulfurization or wet sulfurization.
4. The grading method of heavy oil hydroprocessing catalyst according to claim 1, characterized in that: The sulfiding agent used in the sulfidation process of the hydrogenation pretreatment agent, the hydrogenation transition agent and the hydrogenation finishing agent is independently selected from at least one of H2S, mercaptans, disulfides, polysulfides and thiophenecarboxylic acid compounds.
5. The grading method of heavy oil hydroprocessing catalyst according to claim 1, characterized in that: The hydrogenation pretreatment agent uses an inorganic oxide as a carrier and a VIB group metal and / or a VIII group metal as an active component. Based on the weight of the catalyst, the active metal is calculated as oxide, and the VIB group metal is 3wt% to 26wt%, and the VIII group metal is 0.5wt% to 8wt%.
6. The grading method of heavy oil hydroprocessing catalyst according to claim 5, characterized in that: The hydrogenation pretreatment agent also includes an auxiliary agent, and the auxiliary agent is selected from at least one of P, Si, F, and B.
7. The grading method of heavy oil hydroprocessing catalyst according to claim 1, characterized in that: The hydrogenation transition agent uses an inorganic oxide as a carrier, and uses a VIB group metal and / or a VIII group metal as an active component. Based on the weight of the catalyst, the active metal is calculated as oxide, and the VIB group metal is 3wt% to 26wt%, and the VIII group metal is 0.5wt% to 8wt%.
8. The grading method of heavy oil hydroprocessing catalyst according to claim 7, characterized in that: The hydrogenation transition agent also includes an auxiliary agent, and the auxiliary agent is selected from at least one of P, Si, F, and B.
9. The grading method of heavy oil hydroprocessing catalyst according to claim 1, characterized in that: The hydrogenation refining agent uses an inorganic oxide as a carrier, and uses a VIB group metal and / or a VIII group metal as an active component. Based on the weight of the catalyst, the active metal is calculated as oxide, and the VIB group metal is 3wt% to 26wt%, and the VIII group metal is 0.5wt% to 8wt%.
10. The grading method of heavy oil hydroprocessing catalyst according to claim 9, characterized in that: The hydrogenation refining agent also includes an auxiliary agent, and the auxiliary agent is selected from at least one of P, Si, F, and B.
11. The grading method of heavy oil hydroprocessing catalyst according to any one of claims 5, 7 and 9, characterized in that: The inorganic oxide is selected from at least one of aluminum oxide and silicon oxide, the VIB group metal is selected from at least one of W and Mo, and the VIII group metal is selected from at least one of Co and Ni.
Citation Information
Patent Citations
Method for preparing needle coke material by catalytic cracking slurry
CN103013567B
Hydrogenation catalyst grading method and heavy oil hydrotreatment method
CN105623717A
A method for grading catalysts for heavy oil hydrotreating
CN111196934B
Grading method and application of solid-removal catalytic slurry oil hydrodesulfurization catalyst
CN114984970A
Hydrogenation desulfurization and dearomatization catalyst, system and preparation method thereof, and diesel hydrogenation desulfurization and dearomatization method
CN105478145A